Phylogeography of Dendrolimus punctatus (Lepidoptera: Lasiocampidae): Population differentiation and last glacial maximum survival. Issue 13 (19th June 2019) - Li, Jing; Jin, Qian; Zhu, Geng‐ping; Jiang, Chong; Zhang, Ai‐bing
Abstract: Although the Masson pine moth, Dendrolimus punctatus, is one of the most destructive forest pest insects and is an endemic condition in China, we still do not fully understand the patterns of how its distribution range varies in response to Quaternary climatic oscillations. Here, we sequenced one maternally inherited mitochondrial gene ( COI ) and biparentally inherited nuclear data ( ITS1 and ITS2 ) among 23 natural populations across the entire range of the species in China. A total of 51 mitotypes and 38 ribotypes were separately obtained using mtDNA and ITS1 data. Furthermore, significant phylogeographical structure ( N ST > G ST, p < 0.01) were detected. The spatial distribution of mitotypes implied that two distinct groups existed in the species: one in the southwest distribution, including 10 locations, and the other located in the northeast region of China. It is suggested, therefore, that each group was derived from ancestors that occupied different isolated refugia during previous periods, possibly last glacial maximum. Mismatch distribution and Bayesian population dynamics analysis suggested the population size underwent sudden expansion, which is consistent with the results of ecological niche modeling. As a typical phytophagous insect, the history of population expansion was in accordance with the host plants, providing abundant food resources and habitat. Intraspecific success rate of barcoding identification was lower than interspecific ones, indicating a level of difficulty in barcoding individuals from different populations. However, it still provides an early insight into the pattern of genetic diversity within a species. OPEN RESEARCH BADGES: This article has been awarded an Open Data and Open Materials. All materials and data are publicly accessible via the Open Science Framework athttps://doi.org/10.5061/dryad.2df87g2 . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki . Abstract : Phylogeographic analysis of the Dendrolimus punctatus (Lepidoptera: Lasiocampidae) showed population differentiation affected by the Quaternary climate oscillation and potential refugia during last glacial maximum. As a typical phytophagous insect, the history of population expansion was in accordance with the host plants.